Comparison of short-wave diathermy, Transcutaneous electrical nerve stimulation of electrotherapy methods and exercise therapy in chronic low back conditions - Gh. Abdulkarim, Eman; Taher Ali , Ronak (Diyala Journal of Medicine, 2024)
Background: Low back pain is a significant contributor to global disability, impacting individuals across different age groups. Research suggests that around 80% of people will encounter low back pain at some stage in their lives. This condition is more prevalent among middle-aged and elderly individuals, with a higher occurrence among females. The socioeconomic consequences of low back pain are substantial, including increased healthcare expenses, absenteeism from work, and a diminished quality of life. Objective: To compare the effectiveness of short-wave diathermy with exercise, transcutaneous electrical nerve stimulation with exercise, and exercise alone among patients with chronic low back pain. Patients and Methods: 75 patients who were diagnosed with chronic low back pain, ages 20–50, participated. They were divided into three groups: group A received shortwave with exercise, group B received TENS with exercise, and group C received just exercise. Treatment was given for 12 sessions over a period of 4 weeks. All patients were evaluated before and after treatment using a visual analog scale and the Oswestry Low Back Pain Disability Questionnaire. Results: The results showed that all three interventions were effective in reducing pain and improving physical activities, with varying degrees of success. But also, the result showed that the mean difference for the short wave with exercise is much higher than both the TENS with exercise and the exercise alone types of interventions in each of the different categories, respectively. Conclusion: This study has shown that shortwave exercise is more effective in the treatment of chronic low back pain than TENS with exercise and exercise alone.